2020
DOI: 10.1152/japplphysiol.00296.2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of whole body passive heat stress and arterial shear rate modification on radial artery function in young men

Abstract: We sought to determine how whole-body heating acutely influences radial artery function, characterized using flow mediated dilation (FMD) and low-flow mediated constriction (L-FMC), and the mechanistic role of shear rate modification on radial artery functional characteristics during heating. Eleven young healthy men underwent whole-body heating (water-perfused suit) sufficient to raise core temperature +1°C. Trials were repeated with (Heat+WC) and without (Heat) the application of a wrist cuff located distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…We have previously observed that L-FMC is enhanced immediately (~ 10 min) following a bout of acute dynamic exercise (Elliott et al 2018 ), but it is not known whether this is attributable to an acute enhancement of endothelial function, secondary to changes in the pattern of shear stress (Dawson et al 2012 ). Although we have previously observed that whole-body heating elevated radial artery shear rate, diameter, and blood flow but did not significantly change L-FMC (Alali et al 2020 ). Notably, dynamic exercise with a large muscle mass acutely decreases the conduit artery FMD response for ~ 1 h, although this is not universally observed (Dawson et al 2013 ; Elliott et al 2018 ).…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…We have previously observed that L-FMC is enhanced immediately (~ 10 min) following a bout of acute dynamic exercise (Elliott et al 2018 ), but it is not known whether this is attributable to an acute enhancement of endothelial function, secondary to changes in the pattern of shear stress (Dawson et al 2012 ). Although we have previously observed that whole-body heating elevated radial artery shear rate, diameter, and blood flow but did not significantly change L-FMC (Alali et al 2020 ). Notably, dynamic exercise with a large muscle mass acutely decreases the conduit artery FMD response for ~ 1 h, although this is not universally observed (Dawson et al 2013 ; Elliott et al 2018 ).…”
Section: Introductionmentioning
confidence: 52%
“…This may explain the acutely increased radial L-FMC in the immediate post-exercise period (Elliott et al 2018 ). Interestingly, acute whole-body heat stress was also observed to increase radial artery diameter, blood flow and anterograde SR during, however, no significant change in L-FMC was noted (Alali et al 2020 ). However, there are important differences in the hemodynamic, thermoregulatory, and cellular signalling responses to acute exercise and whole-body heating (Cullen et al 2020 ) that may explain the divergent L-FMC results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations